Hubungan Komunikasi Interpersonal Tutor dengan Hasil Belajar Bahasa Inggris Paket B Kelas VIII di PKBM Sakido - Riska Afriana; Wisroni Wisroni; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is based on the low learning outcomes of the study participants Paket B in PKBM Sakido Nagari Koto Alam District Pangkalan Lima Puluh Kota, this is allegedly due to interpersonal communication tutor. The objectives of this research are (1) to describe the interpersonal communication of tutor, (2) to describe the learning result of the learning community, and (3) to see the correlation between the interpersonal communication of the tutor and the learning result of the studying citizen. This study includes correlational quantitative research. The population in this study is the residents learn Paket B Class VIII. Data collection techniques with questionnaires arranged in the form of statement sheets. Technique of data analysis using formula of percentage and product moment correlation formula. The result of the research shows that (1) the interpersonal communication of the tutor is still not good, (2) the learning result of the VIII Grade Students in PKBM Sakido is low, and (3) there is a very significant correlation between the interpersonal communication of the tutor and the learners' learning result.